Economidichthys mornosensis, a new freshwater sand-goby from Greece (Teleostei: Oxudercidae) - Freyhof, Jörg; Geiger, Matthias F.; Zogaris, Stamatis (Zootaxa, 2026)
Economidichthys mornosensis, a new species, is described from the Mornos River delta in southwestern Greece. It is related to Economidichthys pygmaeus, from which it is distinguished by having a large black blotch on the first dorsal fin in males, a short perianal organ, and a scaleless back along the complete base of the second dorsal fin. Molecular data suggest that the new species can be distinguished from E. pygmaeus by a minimum K2P distance of 5.7 % in the mtDNA COI barcode region. Economidichthys mornosensis is endemic to a very small area, and potentially Critically Endangered.